Spent coffee grounds compaction process: Its effects on the strength properties of biofuel pellets. (November 2019) - Lisowski, Aleksander; Olendzki, Dariusz; Świętochowski, Adam; Dąbrowska, Magdalena; Mieszkalski, Leszek; Ostrowska-Ligęza, Ewa; Stasiak, Mateusz; Klonowski, Jacek; Piątek, Michał
Abstract: An experiment using spent coffee grounds (SCGs) was performed with moisture (6.2, 22.5, 23.2, and 33.4% w.b.) and die height (42, 52, 62, 72, 82, and 92 mm) as influencing parameters at a stable temperature of 93 °C and speed of 100 mm min −1, and the monitoring curves of pressure-displacements were studied. Both pelletization factors were significant parameters for the maximum pressure and corresponding piston displacements, pellet movement, specific work, pellet density, and breaking strength. An interaction was found between these factors, but the moisture had a greater and nonlinear effect on the agglomeration parameters than the die height, which influenced linearly the change of these parameters. The agglomeration parameters values increased with decreasing moisture and increasing the die height. The results suggest that high-strength fuel pellets (>1.0 MPa) could be produced from SCG at a suitable moisture (<20% w.b.) and die height (60–70 mm). A regressive model linking compressive stress with the fuel pellets' density and the maximum pressure was developed, which revealed that pressure had a greater influence on the pellet's compressive strength than the pellet density did. A novelty of this work was the application of an adjustable orifice length of the die in which the SCGs were compacted. Highlights: A heated piston-cylinder with an adjustable open orifice length was used. SCG moisture and die height had significant effect on agglomeration parameters. Moisture effect was greater than die height, which were nonlinear and linear, respectively. Good fuel pellet strength was obtained at <20% w.b. moisture and 60–70 mm die height.